PEMAHAMAN SISWA SEKOLAH DASAR TERHADAP NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPS : STUDI KULITATIF TENTANG LANDASAN SOSIAL DALAM PEMBELAJARAN IPAS - Herdila; Aramudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
his study aims to describe elementary school students’ understanding of character values in social studies learning integrated into the IPAS (Science and Social Science) subject, as well as to identify supporting factors, challenges, and the implementation of these values in the classroom. A descriptive qualitative method with a case study approach was used, conducted at SDN 009 Sendayan. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results showed that most students understood character values such as responsibility, cooperation, and honesty, although their application varied among individuals. Influencing factors included family environment, school culture, and teaching methods used. Challenges faced included the lack of consistency in applying values outside the classroom and the influence of social media. In conclusion, IPAS learning holds significant potential in instilling character values but requires systematic strategies and support from all parties to ensure holistic and sustainable character development in students.